Immunohistochemical study of tissue factor expression in normal intestine and idiopathic inflammatory bowel disease. Issue 8 (August 1993) - More, L; Sim, R; Hudson, M; Dhillon, A P; Pounder, R; Wakefield, A J
Abstract : AIMS–To investigate the localisation of tissue factor expression in normal and inflamed intestine. METHODS–Serial cryostat sections of tissue taken from patients with Crohn's disease (n = 8), ulcerative colitis (n = 5), and from controls (n = 5) were stained with haematoxylin and eosin and immunostained for tissue factor, collagen type IV, fibrinogen and platelet glycoprotein IIIa. RESULTS–In control tissues tissue factor was present as a continuous layer along the epithelial basal lamina: sections from controls did not immunostain for fibrinogen or platelets. In non-ulcerated inflamed mucosa, tissue factor staining intensified in cases of Crohn's disease and was associated with fibrin deposition. Staining for tissue factor was either patchy or absent in cases of ulcerative colitis and there was no fibrin deposition. This change accompanied the early destruction of the epithelial basal lamina in ulcerative colitis that was not seen in Crohn's disease. In both diseases tissue factor expression in severely inflamed and ulcerated mucosa was present on lamina propria macrophages and vascular endothelium and was associated with fibrin or platelet thrombi. In three of eight cases of Crohn's disease tissue factor expression and thrombi were evident in areas of submucosal vasculitis. These were not seen in adjacent normal vessels. CONCLUSIONS–These observations are consistent with a tissue factor haemostatic barrier in the intestine: this barrier seems to be incomplete or defective in ulcerative colitis. Tissue factor expression by macrophages and endothelial cells may be important, particularly in the microvascular thrombosis and induration which are characteristic of Crohn's disease.